Teknologi Komunikasi Baru Dan Industri Event: Dampak Dan Tantangan (Studi Kasus Sanur Village Festival Bali, Indonesia) - Wulandari, Putu Eka Yanthi; Kanzulfikar, Achmad (KOMUNIKA, 2021)
Promotions use conventional mass media such as television, printed newspapers and radio to communicate with the public but now the presence of new media causes big changes in organization’s promotion behavior. An organization starts using new communication technology impacts to event industry in the case Sanur Village Festival. Sanur Village Festival (SVF) is a community event founded by Sanur Development Foundation (YPS) since 2006, which is a combination of severas large scale activities involving food festival, creative economy exhibition, various contest and competitions, art and cultural attractions, music as well as various types of environmentally friendly activities. This event created to re-brand Sanur as one of the oldest tourist destination in Bali and increase tourist visit since 2005 after Bali Bombing I and II. This paper also explains the how Sanur Village Festival manager their official website and social media to help them increasing tourist awareness of thif event that lead the increasing tourist visit in Bali especially Sanur.